Early Modern Authorship and Prose Continuations - Simonova, N. author. aut Link
VII, 225 p.
Keywords: The first in-depth account of fictional sequels in the seventeenth and eighteenth centuries, this examines cases of prose fiction works being continued by multiple writers, reading them for evidence of Early Modern attitudes towards authorship, originality, and literary property.